Colistin heteroresistance in Enterobacter cloacae is regulated by PhoPQ‐dependent 4‐amino‐4‐deoxy‐l‐arabinose addition to lipid A. Issue 6 (10th April 2019) - Kang, Katie N.; Klein, Dustin R.; Kazi, Misha I.; Guérin, François; Cattoir, Vincent; Brodbelt, Jennifer S.; Boll, Joseph M.
Summary: The Enterobacter cloacae complex (ECC) consists of closely related bacteria commonly associated with the human microbiota. ECC are increasingly isolated from healthcare‐associated infections, demonstrating that these Enterobacteriaceae are emerging nosocomial pathogens. ECC can rapidly acquire multidrug resistance to conventional antibiotics. Cationic antimicrobial peptides (CAMPs) have served as therapeutic alternatives because they target the highly conserved lipid A component of the Gram‐negative outer membrane. Many Enterobacteriaceae fortify their outer membrane with cationic amine‐containing moieties to prevent CAMP binding, which can lead to cell lysis. The PmrAB two‐component system (TCS) directly activates 4‐amino‐4‐deoxy‐l ‐arabinose (l ‐Ara4N) biosynthesis to result in cationic amine moiety addition to lipid A in many Enterobacteriaceae such as E. coli and Salmonella . In contrast, PmrAB is dispensable for CAMP resistance in E. cloacae . Interestingly, some ECC clusters exhibit colistin heteroresistance, where a subpopulation of cells exhibit clinically significant resistance levels compared to the majority population. We demonstrate that E. cloacae lipid A is modified with l ‐Ara4N to induce CAMP heteroresistance and the regulatory mechanism is independent of the PmrABEcl TCS. Instead, PhoPEcl binds to the arnBEcl promoter to induce l ‐Ara4N biosynthesis and PmrAB‐independent addition to the lipid A disaccharolipid. Therefore, PhoPQEcl contributes to regulation of CAMP heteroresistance in some ECC clusters. Abstract : Enterobacter cloacae acquires resistance to conventional antibiotic treatments and has demonstrated heteroresistance to colistin, which is a cationic antimicrobial peptide used to supplement our dwindling antibiotic arsenal. The PhoPQ two‐component system contributes to colistin heteroresistance in E. cloacae . Here we show that PhoP directly binds to the arn promoter to induce transcription, which culminates in modification of lipid A and colistin heteroresistance.